Effect of carrageenan on the water holding capacity of cured hams - Panganiban, Cherry C.
The possibility of incorporating carrageenan powder in cured pork hams was studied. The carrageenan powder was directly added in the pumping solution without altering the ingredients. Phase I of this study used a 500 gram right pork ham (coming from the same hog) as a control sample. The treated ham gave a 100% cooking yield while the control ham gave only 90% cooking yield. The treated ham also yielded a higher water holding capacity of 88% while the control sample had a 68% WHC. Phase II employed the same procedure in Phase I. But duplicates were done using four two kilogram pork legs. One right and one left pork legs for the treated ham as well as for the control samples, all the legs being obtained from one hog only. The average cooking yield and water holding capacity of the treated hams were 87.5% and 58% respectively. While the control hams gave an average cooking yield of 78.5% and 47% water holding capacity. Furthermore, results of the sensory evaluations of the two products indicated a no significant difference between the control and the carrageenan - treated curated pork hams. The treated hams were evaluated as pinkish brown in color, having a slight ham odor, slight smoked flavor, a rubbery texture and a general acceptability of like moderately to like very much. The microbiological examination indicated a moderately greater amount of bacterial growth and minimal yeast and mold contamination in the carrageenan added hams in comparison to the control cured pork hams. Nevertheless, the number of bacterial colonies still falls within the normal range of 300 bacterial colonies.